PERKEMBANGAN PSIKOSOSIAL ANAK USIA SEKOLAH DAN IMPLIKASINYA TERHADAP KESEHATAN MENTAL: TINJAUAN TEORI ERIKSON DAN TANTANGAN KONTEMPORER - Rahmadani; Wahyuni, Sri (Jurnal Psikologi Jambi, 2025)
Abstract. Children's psychosocial development is a crucial aspect of personality formation, social skills, and mental health. This article explores the stages of psychosocial development in children based on Erik Erikson's theory and identifies various risk and protective factors affecting the mental health of school-aged children. The study employs a literature review. The findings reveal that healthy psychosocial development is influenced by positive parenting, supportive social environments, and active involvement from both schools and families. Conversely, academic pressure, family conflicts, and lack of emotional regulation contribute to mental disorders such as anxiety, depression, and ADHD. Early detection and interventions involving families and schools are essential to support children’s optimal psychosocial growth.